IMPLEMENTASI KEBIJAKAN PENGEMBANGAN KAWASAN BANTUL KOTA MANDIRI - , Yohanes Nunung Dwi S, M. Sani Roychansyah ST., M.Eng. D.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In 2002, the Government of Bantul Regency has initiated a plan to develop the area of Bantul Kota Mandiri (BKM) to be a satellite town to anticipate the urban sprawl of Yogyakarta. The aims of this study are (1) to describe the implementation of the governmentâs policies in making the BKM plan into real